Work-Life Balance, Compensation, and Employee Performance: The Mediating Effect of Job Satisfaction in the Procurement Division of Denpasar City Government - Arimbawa, Anak Agung Gede Alit; Wijana, I Made Dauh; Landra, Nengah; Imbayani , I Gusti Ayu (Golden Ratio of Human Resource Management, 2026)
This study explores the influence of work-life balance and compensation on employee performance, considering job satisfaction as a mediating variable in the context of the public sector. A quantitative approach was applied through a survey of 60 civil servants in the Procurement Division of the Denpasar City Government. The data were gathered through questionnaires distributed via Google Forms and analyzed using SmartPLS 4 software. The results showed no significant effect of work-life balance on employee performance, either directly or indirectly through job satisfaction. In contrast, while compensation showed no direct effect on performance, it positively influenced performance indirectly through the mediating role of job satisfaction. These findings highlight the crucial mediating role of job satisfaction in improving employee performance, particularly in relation to compensation.